2015
DOI: 10.7225/toms.v04.n02.002
|View full text |Cite
|
Sign up to set email alerts
|

Familiarisation Aboard Ships of Croatian and Montenegrin Officers

Abstract: New officers joining the ship must be aware of their obligations regarding information of security and safety on board. Furthermore, familiarisation includes technical skill related to ships’ equipment. Because of the lack of time during handover due to a short time of cargo operations in port, handover is often inadequate. Familiarisation should last more than a month. Officers’ contracts are usually shorter than familiarisation process. Familiarisation time and lack of familiarisation are considered as perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…These findings echo those of Vidan et al (2015) which revealed that 58% of respondents in a questionnaire study reported a handover duration of 6 , hours or less. Moreover, the safe-manning requirements do not require any redundancy of personnel and consequently handovers are conducted alongside seafarers’ work, normally while the vessel is in port – a period known to be particularly work-intensive.…”
Section: Work Locationsupporting
confidence: 84%
“…These findings echo those of Vidan et al (2015) which revealed that 58% of respondents in a questionnaire study reported a handover duration of 6 , hours or less. Moreover, the safe-manning requirements do not require any redundancy of personnel and consequently handovers are conducted alongside seafarers’ work, normally while the vessel is in port – a period known to be particularly work-intensive.…”
Section: Work Locationsupporting
confidence: 84%
“…A recent research [6] revealed that familiarisation time does not depend on the education of officers, as similar responses are provided by high-school diploma-holders and higher-education degree-holders. • Out of 28 officers with less than 4 years of sea service (7%), 14 officers responded "yes" (50%), and 14 officers responded "no" (50%) • Out of 116 officers with 4 -10 years of sea service (29%), 88 responded "yes" (75.86%), whereas 28 officers responded "no" (24.14%) • Out of 140 officers with 10 -15 years of sea service (35%), 94 responded "yes" (67.15%), and 46 responded "no" (32.85%) • Out of 116 officers with sea service longer than 15 years (29%), 92 officers responded "yes" (73.3%), whereas 24 responded "no" (20.7%) .…”
mentioning
confidence: 89%
“…familiarisation agenda [6]. The SOLAS convention defines the minimum requirements regarding the quantity and features of the ship equipment and devices.…”
mentioning
confidence: 99%
See 2 more Smart Citations